Frequency scan analysis supported by a possibility theory-based approach - Romero Quete, Andrés Arturo (2018)
This paper describes a procedure used to identify the states of a power system that lead to harmonic resonance. The proposed methodology results from an application of the possibility theory which aims to extend the capabilities of the classic frequency scan concept. With the proposed approach, the frequency scan provides more useful information on the harmonic behavior of a power system in contexts where load characteristics are known with uncertainty. To exemplify the potential of this proposal, a case study based on a 14-bus standard test system for harmonic analysis is presented. The states of the power system that lead to harmonic resonance are assessed within the possibility theory framework. Additionally, this paper introduces a risk measure of harmonic resonance based on possibility and necessity fuzzy measures.